Genotype-by-environment interaction studies for yield and Aspergillus resistance in groundnut (Arachis hypogaea) using AMMI and GGE biplots - YADAWAD, ARATI; BHAT, RAMESH (The Indian Journal of Agricultural Sciences, 2026)
The present study was carried out during rainy (kharif) and summer seasons of 2019, 2020 and 2021 at three test locations of Dharwad, Belagavi and Bagalkot districts of Karnataka intended to assess the genotype by environment interaction (GEI) effects to identify high yielding and stable lines with Aspergillus resistance in groundnut (Arachis hypogaea L.) through AMMI and GGE biplots. Seventy-four advanced groundnut lines (F4–F6) derived from the cross between, GPBD 4, Spanish bunch variety resistant to rust and LLS but highly susceptible to Aspergillus infection and ICGV 2266, tolerant to Aspergillus infection were field evaluated. Multi environmental trials were conducted at three locations namely Dharwad, Bagalkot and Belagavi districts of Karnataka following randomised complete block design (RCBD) with two replications. Significant variability was revealed for pod yield, shelling percentage and Aspergillus infection percentage at individual locations and seasons. Pooled analysis of variance revealed highly significant (p